L’éloge du fleuve. La Seine et ses bords, par C. Nodier entre album pittoresque et mémoire géographique - Sukiennicka, Marta (Studia Romanica Posnaniensia, 2023)
The article examines the question of the authorship and generic classification of La Seine et ses bords (1836). This work is commonly misattributed to Charles Nodier, but the most likely author is Alexandre Mure de Pélanne, who in 1835 published a similar essay on the Saône River. The comparison of both works shows a clear difference in their perspectives: La Saône et ses bords, with an emphasis on the his- torical context, meets the generic criteria of album pittoresque (picturesque album), whereas a focus on topography and hydrology of La Seine et ses bords brings it closer to the genre of mémoire géographique (geographical memoir). The scientific scope of La Seine et ses bords also distinguishes it from Nodier’s and Taylor’s Voyages pittoresques et romantiques dans l’ancienne France, the most famous cycle of Romantic journeys through France.